8.6k views
0 votes
SOMEONE PLEASE HELP! I don’t know how to do this !

SOMEONE PLEASE HELP! I don’t know how to do this !-example-1
User Earline
by
5.5k points

1 Answer

2 votes

9514 1404 393

Answer:

136

Explanation:

The x-value at one end of the beam will be where f(x) = 0.

0 = -x²/272 +17

x² = 17(272) = 4624

x = ±√4624 = ±68

The beam extends from x=-68 to x=68, so has a width of ...

68 -(-68) = 136

__

Note that the x in the equation for f(x) is not the same as the x in the picture corresponding to width.

User Mohammad Fneish
by
5.0k points